Analysis of Foreign Aid Effectiveness for School Education Improvement and Economic Growth of Nepal - Acharya, Bisna; Poudel, Omkar; Acharya, Pradeep; Kharel, Khom Raj; Kharel, Suman (Nepal Journal of Multidisciplinary Research, 2024)
Background: Nepal is struggling to improve its education system due to financial deficiency, social disparities, and political instability. The government relies heavily on international aid for education improvement. Nepal’s education system shows foreign aid’s potential and limitations in sustainable development. Foreign aid, GDP per capita, and government spending affect Nepalese youth literacy and gross enrollment rates. This aims to examine the aid effectiveness in school enrollment and GDP growth in Nepal. Methods: This study has employed an econometric approach based on ARDL and Granger causality tests. Model I focuses on youth literacy rates as a measure of educational outcomes, while Model II examines gross enrollment ratios to assess access to education. Results: The results reveal a significant long-term role of foreign aid in improving literacy outcomes, whereas GDP per capita emerges as a critical determinant of enrollment. Granger causality tests highlight bidirectional relationships, showing how literacy improvements influence foreign aid allocation and GDP growth. The findings underscore the importance of aligning aid strategies with local priorities and enhancing the efficiency of public spending to achieve sustained educational improvements. Conclusion: This study contributes to human capital theory by exploring the interplay between education and economic development, emphasizing the need for targeted, sustainable interventions. Future research should focus on the role of institutional quality and demographic disparities in shaping education outcomes. Novelty: This study offers a comprehensive analysis of aid efficacy and its congruence with local requirements by incorporating perspectives from local educators, students, policymakers, and donor organizations.